On a mathematical model of dissociative adsorption and associative desorption - Ambrazevičius, Algirdas; Eismontaitė, Alicija (Lietuvos matematikos rinkinys, 2012)
A mathematical model of dissociative adsorption and associative desorption for diatomic molecules is considered. The model is described by a system of parabolic and ordinary differential equations. The existence and uniqueness theorem of the classical solution is proved.
Keywords: parabolic and ordinary differential equations; surface reactions